Edukasi kesehatan reproduksi remaja di MA YPI Katibung - Yunitasari, Eva; Raminda , Santri; Wahyuni , Devita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Adolescents are people aged between 10 and 19 years. Adolescence is a transition period between childhood and adulthood. Some adolescents say they do not know about the importance of maintaining reproductive health. Purpose: To provide health education as an effort to increase knowledge of reproductive health problems in adolescents. Method: The implementation of this activity goes through several stages, namely asking for permission from the school to conduct counseling to adolescents (students) of MA YPI Katibung and explaining the importance of knowledge/understanding of sexual health and adolescent reproductive health issues. In the implementation stage, all participants were given material presentations using lecture and presentation methods. Furthermore, it was carried out with discussion and question and answer sessions. Results: From the results of the questions and answers conducted by the moderator, most participants already understood the reproductive health material and they could provide examples of the application of maintaining reproductive health in adolescents. Conclusion: Health education can increase knowledge of reproductive health problems in adolescents and make adolescents behave positively. Keywords: Adolescents; Health Education; Reproductive Health Pendahuluan: Remaja adalah orang yang berusia antara 10 dan 19 tahun. Masa remaja adalah masa transisi antara masa kanak-kanak dan dewasa. Beberapa remaja mengatakan mereka tidak tahu tentang pentingnya menjaga kesehatan reproduksi. Tujuan: Memberikan penyuluhan kesehatan sebagai upaya meningkatkan pengetahuan masalah kesehatan reproduksi pada remaja. Metode: Pelaksanaan kegiatan ini melalui beberapa tahapan yaitu meminta ijin kepada pihak sekolah untuk melakukan penyuluhan kepada remaja (siswa) MA YPI Katibung dan menjelaskan pentingnya pengetahuan/pemahaman masalah kesehatan seksualitas dan kesehatan reproduksi remaja. Tahap pelaksanaan seluruh peserta diberikan pemaparan materi dengan metode ceramah dan presentasi. Selanjutnya dilakukan dengan sesi diskusi dan tanya jawab. Hasil: Dari hasil tanya jawab yang dilakukan moderator sebagian besar peserta sudah memahami materi kesehatan reproduksi dan mereka bisa memberikan contoh penerapan menjaga kesehatan reproduksi pada remaja. Simpulan: Penyuluhan tentang kesehatan dapat meningkatkan pengetahuan masalah kesehatan reproduksi pada remaja dan menjadikan remaja berperilaku positif.